2010
DOI: 10.1159/000321171
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Acute Kidney Injury following Cardiac Surgery and Related Risk Factors in Chinese Patients

Abstract: Background/Aims: Acute kidney injury (AKI) following surgery is a major complication, but the prevalence and risk factors in the Asian population are unclear. Recently, a consensus definition of AKI (AKIN) was proposed. We studied a cohort of cardiac surgery patients and identified AKI by AKIN and associated risk factors. Methods: We retrospectively evaluated 1,056 consecutive patients undergoing cardiac surgery in Renji Hospital, Shanghai Jiaotong University School of Medicine, Shanghai, China from January 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
19
3
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 53 publications
10
19
3
2
Order By: Relevance
“…We found a significant reduction in AKI with Nephrology On-Site and a baseline AKI incidence with Nephrology On-Demand of 31.9%, similar to previous studies [3,4]. As expected, a higher positive impact was achieved in patients with intermediate risk.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…We found a significant reduction in AKI with Nephrology On-Site and a baseline AKI incidence with Nephrology On-Demand of 31.9%, similar to previous studies [3,4]. As expected, a higher positive impact was achieved in patients with intermediate risk.…”
Section: Discussionsupporting
confidence: 91%
“…With Nephrology On-Site, there was a trend towards a higher proportion of patients receiving RST, together with some parameters of earlier dialysis, even though the proportion of severe AKI was lower than previously reported [4]. Although no specific criterion was used to determine when RST should be started, in our center patients with RIFLE-I/AKIN-2 plus an unfavorable state (mechanical ventilation, hemodynamic instability, inputs higher than urine output or sepsis) are usually considered for RST, and with Nephrology On-Site this recognition process might be accelerated.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…), multiple organ failure and other factors. [16][17][18][19][20] Therefore, it is necessary to strictly monitor patient's hemodynamics to reduce volatility of renal perfusion. In addition, for high-risk patients with insufficient effective circulating blood volume, these drugs should be used with caution at early stage of post-operation in addition to closely monitoring changes in renal function.…”
Section: Discussionmentioning
confidence: 99%
“…Although some studies have reported the short-term outcomes of cardiac surgery in China [6], few have investigated the long-term outcomes of CSA-AKI [7], which is important to plan follow-up strategies and to formulate and adjust healthcare policies in China. Here, a historical cohort study of patients who underwent cardiac surgery in a tertiary general hospital in southeast China was conducted to investigate the long-term survival rate and the incidence of stages 3-5 CKD and to analyze the impact of CSA-AKI on these outcomes.…”
Section: Introductionmentioning
confidence: 99%